Phylogeny and classification of the Sciaroidea (Diptera: Bibionomorpha): Where do we stand after Amorim & Rindal (2007)? - Jaschhof, Mathias (Contributions to Entomology = Beiträge zur Entomologie, 2011)
A paper on the phylogeny of the Sciaroidea by D. Amorim and E. Rindal from 2007 is reviewed. The phylogenetic hypothesis derived from morphological quantitative analysis is used by these authors to propose a new classification of the Sciaroidea which differs significantly from previous classifications. In the present review it is shown by way of examples that the data matrix used by Amorim and Rindal is fatally flawed in terms of both the employed taxa and characters. As a result, the analysis is not repeatable and the hypothesis resulting from it is neither testable nor rebuttable. It is suggested that the paper in question should not be used as a basis for changes in the traditional classification of the Sciaroidea. Keywords Diptera, Sciaroidea, phylogeny, family classification, review.